Road verges as habitat for the Cabrera vole: a vegetation analysis - Santos, Sara M. (2006)
The Cabrera vole (Microtus cabrerae Thomas 1906) is a threatened rodent showing a fragmented distribution in the Iberian Peninsula. Although specific microhabitat requirements have been pointed out for the species, road verges are sometimes occupied. The aim of this study is the identification and comparison of the floristic composition between road verge and meadow colonies. Vegetation was sampled in 26 colonies in five geographical areas. Cover of herbaceous stratum was sampled in plots of 1x1 m. Several variables related to plant diversity, Raunkiaer life-forms, taxonomic groups, disturbance and soil properties were measured. Data analysis was undertaken with Mann-Whitney tests and ordination techniques (DCA and CCA). Road verge and meadow colonies of Cabrera vole showed differentiated herbaceous vegetation composition. Indicator species of road verge colonies corresponded mainly to annual grasses and forbs, ruderal and nitrophilous species, along with a few perennials. In meadows, perennial grasses and moisture indicative species were more common. Although road verges showed higher diversity in the most usually consumed grasses in the vole’s diet, they suggested several disadvantages as habitat, such as higher disturbance, lower moisture availability during summer and reduced colony surface.